The botany of desire : a plant's eye view of the world - Pollan, Michael (New York : Random House, 2001)
"An Idaho farmer cultivates Russet Burbank potatoes so that a customer at a McDonald's half a world away can enjoy a long, golden french fry. A gardener plants tulip bulbs in the fall and, come spring, has a riotous patch of color to admire. Two straightforward examples of how humans act on nature to get what we want. Or are they? What if those potatoes and tulips have evolved to gratify certain human desires so that humans will help them multiply? What if, in other words, these plants are using us just as we use them?".
"In this narrative that blends history, memoir, and the best science writing, Pollan tells the story of four domesticated species - the apple, the tulip, marijuana, and the potato - from the point of view of the plants. All four species are deeply woven into the fabric of our everyday lives, and Pollan illustrates how each has evolved a survival strategy based on satisfying one of humankind's most basic desires. The apple gratifies our taste for sweetness; the tulip attracts us with its beauty; marijuana offers intoxication; and the genetically modified potato gives us a sense of control over nature. And just as we've benefited from these plants, the plants, in the grand co-evolutionary scheme that Pollan evokes, have done remarkably well by us."--BOOK JACKET.
Introduction: The Human Bumblebee -- Ch. 1. Desire: Sweetness/Plant: The Apple -- Ch. 2. Desire: Beauty/Plant: The Tulip -- Ch. 3. Desire: Intoxication/Plant: Marijuana -- Ch. 4. Desire: Control/Plant: The Potato.
Includes bibliographical references (pages [247]-256) and index.
ARC
Department of architecture
Keywords: Human-plant relationships